Arise of the sexual size dimorphism in juvenile White-throated Dipper (Cinclus cinclus) in Northern Slovakia - Michal Baláž; Lucia Hrčková; Mária Balážová (Tichodroma)
Sexual size dimorphism is relatively common in different taxonomic groups of birds, and it is present even in species with no visual differences in colour and/or type of feathers. The White-throated Dipper (Cinclus cinclus) is one of these species. Differences in the length of several body parts are commonly used in sex determination. Males are significantly larger than females even in juveniles and 12-days-old nestlings. However, we have no information on the differences in younger nestlings and differences can be also found in adults from different populations. During 2016–2018 we measured 64 three-, six-, and ten-days old nestlings (31 females and 33 males) and 94 adult (46 females and 48 males) birds. The sex of nestling was determined using genetic methods. The adult birds exhibited significant differences in wing length (males: 89–98 mm, average 93.6 mm; females: 81–89 mm, average 85.1 mm), tail length (males: 50–60 mm, average 55.7 mm; females: 45–56 mm, average 50.5 mm) and tarsus length (males: 32.5–37.1 mm, average 35.1 mm; females: 31.2–34.8 mm, average 32.9 mm). No differences were found in beak length or other body parts of the three-day old and six-day old nestlings. However, ten-day-old nestlings showed significant differences in wing length (males: average 2.6 mm; females: average 2.4 mm) and tarsus length (males: average 27.6 mm; females: average 26.5 mm), which represent the earliest published age at which this species shows pronounced sexual differences. Furthermore, the documented sexual size differences in adult birds can improve sex determination under regional Central European conditions.